MEASURING ANXIETY TOWARDS RESEARCH AND THESIS WRITING AMONG ISLAMIC COLLEGE STUDENTS: A MIXED-METHODS STUDY - Mudra, Heri; Sastria, Emayulia (UIN Sumatera Utara Medan, 2023)
It is unquestionable that research and thesis writing anxiety has negative impacts on academic success. Such academic anxiety needs a serious concern by measuring it as a beginning step to determine appropriate research and thesis writing strategies. Therefore, this study aimed at measuring the types and levels concerning anxiety towards research and undergraduate thesis writing among students in an Islamic college. Through a mixed-methods design, 450 students from various majors at a state-owned college were asked to complete a questionnaire and 10 students were involved in a semi-structured interview. The quantitative data were analyzed by determining means, SD, and frequency levels and a content analysis was applied to analyze qualitative data. The results revealed perceived utility and competence as the most common type experienced by students during a field research and thesis writing. On the other hand, the students are able to work with library-related practice as it has the lowest mean score. Regarding qualitative result, it is stated that there are problem that emerge during the field research and thesis writing, including fear of writing, library, statistics, and field research. Fortunately, the students are able to cope with the problems by undertaking several related strategies, including conducting regular practice, comprehending online resources, and utilizing online application. In short, it is implied that such academic anxiety can be avoided by the students and it is recommended that future research has to focus on determining research and thesis writing strategies.